Case report: Identification of Hepatitis B Virus in the cerebrospinal fluid of neuromyelitis optica spectrum disorders and successful treatment with ofatumumab and inebilizumab - Cai, Linjun; Liu, Xu; Zhou, Hongyu; Li, Jinmei; Zhou, Dong; Hong, Zhen (Frontiers in Immunology, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare demyelinating disease of the central nervous system (CNS), primarily affecting vision, the spinal cord, and the brainstem. Viral infection may trigger NMOSD. Here, we report the case of a 34-year-old female presenting with a range of symptoms including vomiting, diarrhea, difficulty swallowing, coughing while drinking, fatigue with an unsteady gait, diplopia, hearing loss, left-sided facial paralysis, breathing difficulties, and hoarseness of voice.The serum HBV DNA concentration, determined by quantitative PCR analysis, exceeded 5×10 7 IU/ml, while the HBV DNA concentration in CSF surpassed 4.48×10 2 IU/ml.Next-generation sequencing (NGS) revealed 1,528 HBV sequences in DNA analysis and 6 sequences in RNA analysis in the CSF. Serum aquaporin-4 antibody (AQP4-Ab) titer was 1:10, and the CSF titer was 1:3.2. Brain magnetic resonance imaging (MRI) indicated high signal intensities in the brain stem, medulla bulbar, and left cerebellar middle foot with mild limited diffusion. The patient received antiviral and hepatoprotective medications before undergoing high-dose methylprednisolone pulse therapy.However, the patient did not respond well to the first-line treatment. Subsequently, the patient underwent treatment with ofatumumab and inebilizumab. Throughout the follow-up period, there was a gradual improvement in neurological symptoms, with no reactivation of hepatitis B or deterioration of liver function observed